'It feels like being trapped in an abusive relationship': bullying prevalence and consequences in the New Zealand senior medical workforce: a cross-sectional study. Issue 3 (19th March 2018) - Chambers, Charlotte N L; Frampton, Christopher M A; McKee, Martin; Barclay, Murray
Abstract : Objectives: To estimate prevalence of and factors contributing to bullying among senior doctors and dentists in New Zealand's public health system, to ascertain rates of reporting bullying behaviour, perceived barriers to reporting and the effects of bullying professionally and personally. Design: Cross-sectional, mixed methods study. Setting: New Zealand. Participants: Members of the Association of Salaried Medical Specialists (40.8% response rate). Main outcome measures: Prevalence of bullying was measured using the Negative Acts Questionnaire (revised) (NAQ-r). Workplace demands and level of peer and managerial support were measured with the Health and Safety Executive Management Standards Analysis tool. Categories of perpetrators for self-reported and witnessed bullying and barriers to reporting bullying were obtained and qualitative data detailing the consequence of bullying were analysed thematically. Results: The overall prevalence of bullying, measured by the NAQ-r, was 38% (at least one negative act on a weekly or daily basis), 37.2% self-reported and 67.5% witnessed. There were significant differences in rates of bullying by specialty (P=0.001) with emergency medicine reporting the highest bullying prevalence (47.9%). The most commonly cited perpetrators were other senior medical or dental specialists. 69.6% declined to report their bullying. Bullying across all measures was significantly associated with increasing work demands and lower peer and managerial support (P=0.001). Consequences of bullying were wide ranging, affecting workplace environments, personal well-being and subjective quality of patient care. Conclusions: Bullying is prevalent in New Zealand's senior medical workforce and is associated with high workloads and low peer and managerial support. These findings help identify conditions and pressures that may encourage bullying and highlight the significant risk of bullying for individuals and their patients.